Archivar lo efímero: La huella, el tejido y la refracción - Atuesta, Juliana (2025)
This article focuses on the challenge of building a history of contemporary dance in a country like Colombia, where we lack a documentary background and a legacy of historical construction based on the institutionalization of the archive. For this end, we analyze in the first place the notion of archive in the universe of Western dance, to later review its possibilities and expansive powers that transcend its materiality. "Archiving the ephemeral" refers to the dilemma of turning dance into archive, when it is ephemeral in nature, and thus opens the possibilities of building not a history, but a conglomerate of histories that sustain their unfolding in memory, orality, movement, gestures and specially in the body. This analysis focuses on the study of three scenic projects of Colombian artists, through which these questions are projected and raised within a theoretical, practical and scenic framework: Huellas y Tejidos (20113), Refracciones (2022) and Camila Sepultada en la Luz (2024).